2017
DOI: 10.1016/j.ijdevneu.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐enhanced MR imaging (MEMRI) combined with electrophysiology in the study of cross‐modal plasticity in binocularly blind rats

Abstract: Our study aimed to determine and verify the establishment of visual to auditory cross-modal plasticity using manganese-enhanced MR imaging (MEMRI) combined with examinations of the visual evoked potential (VEP), auditory brainstem response (ABR) and bilateral visual cortex response to a bilateral auditory stimulus (AVR). Fourteen healthy male Sprague-Dawley newborn rats were randomly divided into 2 groups (n=7 per group). Optic nerve transection was performed in the 7 rats of Group A three weeks after birth to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…With an increase in detectable projections from both the retina and visual cortex following enucleation, this study demonstrates the ability of MEMRI to not only map the visual system, but also to detect finer neuroplastic changes. Other studies have since demonstrated the ability of MEMRI to detect sensory system-wide neuroplastic changes (Tang et al, 2017a,b).…”
Section: Memri In Cns Imagingmentioning
confidence: 99%
“…With an increase in detectable projections from both the retina and visual cortex following enucleation, this study demonstrates the ability of MEMRI to not only map the visual system, but also to detect finer neuroplastic changes. Other studies have since demonstrated the ability of MEMRI to detect sensory system-wide neuroplastic changes (Tang et al, 2017a,b).…”
Section: Memri In Cns Imagingmentioning
confidence: 99%
“…Subsequent studies demonstrated the use of in vivo MEMRI tract tracing for retinotopic mapping at submillimeter resolution (Chan et al, 2011) (Figure 3B), and for monitoring primary versus secondary degeneration after partial transection of the optic nerve (Chan et al, 2017). With these premises, MEMRI can serve as an in vivo imaging model system to evaluate neuroprotective approaches to the injured visual system (Mansergh et al, 2014; Van der Merwe et al, 2016, van der Merwe et al, 2019), as well as to trace neuroplasticity (Immonen et al, 2008; Chan et al, 2012a; Tang et al, 2017b) and regenerated axons along the visual pathway (Liang et al, 2011; Sandvig et al, 2011, 2012; Sandvig and Sandvig, 2014; Komatsu et al, 2017). MEMRI can be combined with diffusion tensor imaging to give complementary information about injury and regeneration in the adult optic nerve (Thuen et al, 2009).…”
Section: Neuronal Tract Tracingmentioning
confidence: 99%